2003
DOI: 10.1089/15396850360495655
|View full text |Cite
|
Sign up to set email alerts
|

The Lymphatic System in Body Homeostasis: Physiological Conditions

Abstract: The lymphatic system is an organized network composed of functionally interrelated lymphoid tissue, and transportation pathways of tissue fluid/lymph and lymphoid cells. Its main components are 1. migrating dendritic cells, macrophages and lymphocytes, organized lymphoid tissue such as lymph nodes, thymus, spleen, bone marrow, and lymphoid tissue in gut and lungs, liver lymphoid cells, and the dendritic cell network of nonlymphoid organs; 2. vessels (intercellular space, lymphatics, and perivascular spaces); 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
89
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 15 publications
0
89
0
2
Order By: Relevance
“…Lymphedema is a condition in which interstitial fluid flow is severely reduced due to either malformations in the lymphatic system (primary lymphedema) or blockage downstream, such as that which occurs after lymph node resection (secondary lymphedema). The accumulation, rather than clearance, of fluid from the interstitial space results in inflammation and extensive tissue remodeling, lymphatic hyperplasia, and adipocyte growth and lipid accumulation [38,39]. Fluid stagnation in lymphedema also prevents normal immune cell trafficking in the affected tissue, which can exacerbate the pathology.…”
Section: Box 1 Darcy's Lawmentioning
confidence: 99%
“…Lymphedema is a condition in which interstitial fluid flow is severely reduced due to either malformations in the lymphatic system (primary lymphedema) or blockage downstream, such as that which occurs after lymph node resection (secondary lymphedema). The accumulation, rather than clearance, of fluid from the interstitial space results in inflammation and extensive tissue remodeling, lymphatic hyperplasia, and adipocyte growth and lipid accumulation [38,39]. Fluid stagnation in lymphedema also prevents normal immune cell trafficking in the affected tissue, which can exacerbate the pathology.…”
Section: Box 1 Darcy's Lawmentioning
confidence: 99%
“…One type of peripheral tissue with the active afferent limb of the lymphatic system is, for example, the skin, and memory/effector T cells migrate to inflamed skin using CCR4 and CCR10 (8)(9)(10). Classic studies employing cannulation of afferent lymph vessels have shown that CD4 + memory/effector cells make up nearly all cells in the afferent lymph of sheep (6,(11)(12)(13). On the other hand, Debes et al have reported that CD4 + cells, especially naive subsets, migrate from the skin in a CCR7-dependent manner using subcutaneous injection of fluorescent-labeled lymphocytes (14).…”
Section: Introductionmentioning
confidence: 99%
“…Memory/effector T cells become programmed to migrate to extralymphoid tissues to provide defense against invading pathogens and contribute to local inflammation. Classic lymph recirculation studies in sheep have demonstrated that memory/ effector T cells exit extralymphoid tissue and reach the local LNs by traveling through the afferent lymphatics (8)(9)(10). Approximately 10% of all lymphocytes and a major fraction of Ag-experienced T cells that enter an LN do so via the afferent lymph (11,12).…”
mentioning
confidence: 99%